STUDI DESKRIPTIF KELENGKAPAN DOKUMEN REKAM MEDIS RAWAT INAP PADA KASUS BEDAH ORTHOPEDY DI RSUD KOTA SEMARANG - Angga Ferdianto; Lutfiati - (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
The purpose of this study is to find the percentage of completeness in inpatient medical record documents in cases of orthopedic surgery at General District Hospital Semarang. The kind of research is descriptive quantitative. Research design with retrospective analysis approach. The technique of collecting data used is purposive sampling. The variable research consists of all review components in the quantitative analysis. The method of collecting data is observation using cheklist.The method of analysing data is descriptive quantitative analysis.The results of the quantitative analysis shows that there is incompleteness inpatient medical record documents in the case of surgery. Identification review of the highest incompleteness on date of birth found in an output form and anesthesia report is 99%. Authentication review of the highest incompleteness on time in surgical operation reports is 70,7%. The review from documentation of the highest incompleteness on blank found in input and output summary forms is 100%. The important report of the highest incompleteness in input and output summary forms is 100% .